'J'ai mon silence': The interrelations of sound, voice and silence in three short stories by Sylvia Townsend Warner1. Issue 1 (1st June 2021) - Malcolm, David
The interrelations of sound, voice and silence in three realist short stories by Sylvia Townsend Warner from the 1940s are discussed. The stories are 'The Proper Circumstances', 'The Mother Tongue' and 'A Breaking Wave', all published in the posthumous collection One Thing Leading to Another (1984). Warner is shown to be deeply attuned to sound and its absence in her short fiction; these motifs are integrated with other aspects of setting and with character and narration. Both sound in the text and sound of the text are of semantic importance in her work. Warner's presentation of silence as a source of power is remarkable, silence being usually configured as lack of agency. Warner's deployment of silence is related to her status as a lesbian writer.